2022
DOI: 10.3390/ijerph19116496
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Adherence and Health-Related Quality of Life in Patients with Hemophilia in Hong Kong

Abstract: Background: This study aims to identify factors affecting health-related quality of life (HRQoL) in Chinese patients with hemophilia in Hong Kong, and to examine the association between treatment adherence and HRQoL outcomes. Methods: Patients with hemophilia A or B from a non-governmental organization reported their HRQoL and treatment adherence to prophylactic therapy using validated tools. Univariate tests and multivariable regression analysis were used to compare differences in outcomes across clinically r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…32 We have previously reported that poor adherence is correlated with poor self-perception of health and future outlook among patients with haemophilia in Hong Kong. 26 Similarly, our finding in this study that overweight/obese patients have decreased cognitive flexibility might be explained by the association between lifestyle behaviour and cognitive outcomes. 46 Future work should include a prospective and objective assessment of treatment adherence and lifestyle behaviours among patients with haemophilia, and its impact on functional outcomes.…”
Section: Discussionsupporting
confidence: 61%
See 4 more Smart Citations
“…32 We have previously reported that poor adherence is correlated with poor self-perception of health and future outlook among patients with haemophilia in Hong Kong. 26 Similarly, our finding in this study that overweight/obese patients have decreased cognitive flexibility might be explained by the association between lifestyle behaviour and cognitive outcomes. 46 Future work should include a prospective and objective assessment of treatment adherence and lifestyle behaviours among patients with haemophilia, and its impact on functional outcomes.…”
Section: Discussionsupporting
confidence: 61%
“…Although we did not conduct clinical evaluations of mental health disorders in our cohort, our validated screening tool (DASS‐21) showed that one‐fifth of patients reported moderate‐to‐severe depressive or/and anxiety symptoms. We have also previously reported that adult patients with haemophilia in Hong Kong reported poorer quality of life, particularly in the domains of self‐perception, feelings, and perception of the future 26 . Furthermore, this study was conducted during the Coronavirus pandemic; increases in psychological distress were reported during that period in the local population 43 .…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations